Peran Pembiayaan Baitul Maal Wat Tamwil Terhadap Perkembangan Usaha dan Peningkatan Kesejahteraan Anggotanya dari Sektor Mikro Pedagang Pasar Tradisional - Prastiawati, Fitriani; Darma, Emile Satia (Journal of Accounting and Investment, 2016)
The growth and development of economic in Indonesia are not only from big cimpanies or multinationa, but the small business, micro business, and middle business have main problems in financial. To solve the problems, Baitul Maal Wat Tamwil (BMT) comes to give the finance to the micro businessmen easily. The aim of this research was to khow the role of finance given by Baitul Maal Wat Tamwil towards the perception of business development and the welfare improving for the members of BMT from micro sector. The samples of the researches were 119 of the members of BMT finance whose jobs were sellers in traditional market in Bantul Regency. The data used for the research were primary data by distributing questionnaires. The data analysis employs Structural Equation Modelling (SEM). The results reveal that the BMT’s finance does not has significant influence towards the perception of business development and the welfare improving. However, the business growth has significant influence towards the perception of the wefare improving of the members.